2013
DOI: 10.1210/jc.2013-1112
|View full text |Cite
|
Sign up to set email alerts
|

An Independent Positive Relationship Between the Serum Total Osteocalcin Level and Fat-Free Mass in Healthy Premenopausal Women

Abstract: The serum level of total osteocalcin was positively associated with fat-free mass independent of age, fat mass, leptin, and other confounders in premenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Osteocalcin as an osteoblast‐specific protein involved in the regulation of glycolipid and energy metabolism. Studies have shown that the serum osteocalcin levels of postmenopausal women are significantly lower than those of premenopausal women and that lower serum osteocalcin levels are closely associated with metabolic risk factors . In this study, we found that the serum osteocalcin level in postmenopausal women was also negatively correlated with several parameters of glycolipid metabolism.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Osteocalcin as an osteoblast‐specific protein involved in the regulation of glycolipid and energy metabolism. Studies have shown that the serum osteocalcin levels of postmenopausal women are significantly lower than those of premenopausal women and that lower serum osteocalcin levels are closely associated with metabolic risk factors . In this study, we found that the serum osteocalcin level in postmenopausal women was also negatively correlated with several parameters of glycolipid metabolism.…”
Section: Discussionsupporting
confidence: 50%
“…Osteocalcin plays an important role in glucose and lipid metabolism as well as the development of obesity, including abdominal obesity. Although several studies have identified a connection between the serum osteocalcin level and abdominal obesity, W was applied as a measurement parameter in these studies; unfortunately, W has poor accuracy in the evaluation of fat distribution . Another study of 214 postmenopausal Korean women found that serum osteocalcin was negatively correlated with the VFA measured by bioelectrical impedance analysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A human study demonstrated that serum osteocalcin levels in postmenopausal women were lower than those in premenopausal women, suggesting that bone formation decreases with aging (Liu et al . ). By contrast, increased osteocalcin levels have been observed frequently after OVX in rats and during menopausal transition in women (Seifert‐Klauss et al .…”
Section: Discussionmentioning
confidence: 97%
“…Osteocalcin is expressed primarily by osteoblasts, and has been traditionally regarded as a bone formation marker. A human study demonstrated that serum osteocalcin levels in postmenopausal women were lower than those in premenopausal women, suggesting that bone formation decreases with aging (Liu et al 2013). By contrast, increased osteocalcin levels have been observed frequently after OVX in rats and during menopausal transition in women (Seifert-Klauss et al 2012;Tseng et al 2014), because osteocalcin is also released from the bone matrix into the bloodstream during bone resorption, thereby indicating osteocalcin as an additional marker of bone turnover (Neve et al 2013).…”
Section: Discussionmentioning
confidence: 99%